Allelopathic effects of aqueous extracts of leaves of tree marigold (Tithonia diversifolia (Hemsl.) A. Gray) on seed germination and seedling growth of lettuce (Lactuca sativa L.) - Laynez Garsaball, José Alberto (2013)
Some chemical compounds released by plants can to control the presence of other plants in their environment both of their own species and different ones, allelopathy is an important factor in regulating the structure of plant communities, a better understanding of these relationships is critical for appropriate agricultural development. The objective was to determine the effects of aqueous extracts of leaves of tree marigold (Tithonia diversifolia) on seed germination and seedling growth of lettuce (Lactuca sativa L.) cultivar Parris Island. A 15% w/v extract was prepared with leaves of tree marigold gold, it was allowed to stand for 48 h. After, diluting extracts at 0.5, 1.0, 1.5 and 2.0% w/v were obtained and pH and electrical conductivity (S.cm-1 ) were determined. Sowing was carried out in trays covered with a double layer of absorbent paper on which were placed 25 seeds/tray. Irrigation was applied twice per day using leaf extracts. The control treatment received tap water. A randomized complete block design was used with four replications. Seedlings were harvested at 14 days after sowing. pH decreased and electrical conductivity increased with increases in the concentration of leaf extracts. The germination was negatively affected by extracts. A lowering effect was observed on the overall growth of lettuce seedlings.